(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
In the proem of canto eighteen of Hercole, Giovan Battista Giraldi Cinzio addresses the «donne gentili». The octaves that follow recount a «lascivo amore, e fiamme scelerate»; but the intent, the author warns, is not to tarnish the faith of the aforementioned, defined shortly afterwards as inviolable, but rather to define a vice not to be followed. The narrative is intended to serve as an exemplum and the proem is elected as a form of dialogue. Cinzio’s is not the only case within the sixteenth-century chivalric production in which the author, through allocutionary formulas, addresses his readers. In fact, he is accompanied by a series of texts that follow in the wake of the cantari, Boiardo, and Ludovico Ariosto’s Furioso: from Cassio da Narni’s La morte del Danese to Vincenzo Brusantini’s Angelica innamorata, up to the more famous Amadigi by Bernardo Tasso. Each of them establishes a dialogue with the female audience, whether noble or indefinite, no longer exclusively dedicated to working with «l’ago e ’l panno».